The Impact of Electronic Patient File Governance on the Performance and Effectiveness of Health Insurance Companies in Saudi Arabia (The International Journal for Scientific Research, 2026)
This study examines the impact of Electronic Patient File (EPF) governance on the performance and effectiveness of health insurance companies in Saudi Arabia. Grounded in IT Governance Theory, the Resource-Based View, and the DAMA-DMBOK framework, the study adopts a quantitative descriptive-correlational design. Data were collected from 51 employees of health insurance companies and hospital insurance departments using a 20-item Likert-scale online questionnaire distributed via Google Forms. Analysis was conducted using SPSS v.26, employing Cronbach's Alpha (α = 0.921), descriptive statistics, Pearson correlation, and simple linear regression.Results revealed that EPF governance explains 26.6% of the variance in institutional performance (R² = 0.266, β = 0.515, F = 17.719, p = 0.000), confirming a statistically significant positive effect at α ≤ 0.05. The five governance dimensions demonstrated positive correlations with performance indicators ranging from moderate to strong (r = 0.288–0.559, p < 0.05).
Keywords: Electronic Patient File; Health Data Governance; Health Insurance; Organizational Performance; Saudi Arabia; Vision 2030